Airborne Measurements of Contrail Ice Properties—Dependence on Temperature and Humidity. Issue 8 (28th April 2021) - Bräuer, T.; Voigt, C.; Sauer, D.; Kaufmann, S.; Hahn, V.; Scheibe, M.; Schlager, H.; Diskin, G. S.; Nowak, J. B.; DiGangi, J. P.; Huber, F.; Moore, R. H.; et al.
Abstract: The largest share in the climate impact of aviation results from contrail cirrus clouds. Here, the dependence of microphysical contrail ice properties and extinction on temperature and humidity is investigated. Contrail measurements were performed at various altitudes during the 2018 ECLIF II/NDMAX campaign with the NASA DC‐8 chasing the DLR A320. Ice number concentrations and contrail extinction coefficients are largest at altitudes near 9.5 km, typical for short‐ and medium‐range air traffic. At higher altitudes near 11.5 km, low ambient water vapor concentrations lead to smaller contrail particle sizes and lower extinction coefficients. In addition, contrails were detected below 8.2 km near the Schmidt‐Appleman contrail formation threshold temperature. Here, only a small fraction (<15%) of the emitted soot particles were activated into ice. Our observations enhance the understanding of contrail formation near the formation threshold and give a glimpse on the altitude dependence of climate‐relevant contrail properties. Plain Language Summary: Aviation has an impact on our climate and of all components, contrails are the main contributor. In January 2018, we measured contrails during the ECLIF II/NDMAX campaign. The NASA research aircraft DC‐8 flew closely behind the DLR's A320. With a wide range of instruments, we measured trace gases and soot particles emitted by the A320, as well as contrail ice crystals. The data presented here are the most comprehensive contrail data set ever collected during a single flight campaign. The contrail properties are strongly influenced by ambient parameters as well as aircraft and fuel properties. Here, we focus on the influence of environmental conditions such as temperature and humidity on the formation and growth of contrail ice crystals. Therefore, we present and compare ice measurements at three different flight altitudes. For 1–2‐min old contrails, we find a decrease in extinction with increasing altitude. Extinction describes the interaction between contrails and atmospheric radiation. We also find that at the lowest and warmest altitudes only a small part of the emitted soot particles is activated into contrail ice crystals. In the end, our data help to better understand contrail formation and will contribute to the research on sustainable aviation. Key Points: The dependence of contrail ice microphysics and extinction on ambient temperature and humidity is investigated Soot activation fractions in contrails formed at varying ambient temperatures are derived of soot and apparent ice emission indices At altitudes below 8.2 km, we observed contrails formed under incomplete soot activation near the contrail formation threshold temperature